2022
DOI: 10.1111/ijfs.15639
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulated Lippia origanoides essential oil: physiochemical characterisation and assessment of its bio‐efficacy against fungal and aflatoxin contamination as novel green preservative

Abstract: Summary The study explores in vitro antifungal and aflatoxin B1 inhibitory potency of chemically characterised Lippia origanoides EO (LOEO) encompassed in chitosan nanoparticle (CS‐LOEO‐Np). CS‐LOEO‐Np was physico‐chemically characterised through XRD, SEM and FTIR analyses. CS‐LOEO‐Np exhibited improved antifungal and AFB1 inhibitory efficacy (0.05 and 0.045 µl mL−1, respectively) in contrast to LOEO (0.30 and 0.25 µl mL−1, respectively). Bioactivity of LOEO loaded nanoparticle was enhanced as reflected by dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In contrast, the sensory analyses after long storage periods indicated that CHNPs improved the sensory attributes of postharvest products (Martinez-Gonzalez et al, 2020;Melo et al, 2018). For instance, Tiwari et al (2022) reported that CHNPs-Lippia origanoides essential improved the acceptability, color, taste, and flavor of black cumin seeds after 18 months of storage. CHNPs with Pimpinella anisum essential oil improved rice seeds' color, taste, and odor after 1 year of storage (Das, Singh, et al, 2021).…”
Section: Sensory Attributes and Costumer Acceptabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the sensory analyses after long storage periods indicated that CHNPs improved the sensory attributes of postharvest products (Martinez-Gonzalez et al, 2020;Melo et al, 2018). For instance, Tiwari et al (2022) reported that CHNPs-Lippia origanoides essential improved the acceptability, color, taste, and flavor of black cumin seeds after 18 months of storage. CHNPs with Pimpinella anisum essential oil improved rice seeds' color, taste, and odor after 1 year of storage (Das, Singh, et al, 2021).…”
Section: Sensory Attributes and Costumer Acceptabilitymentioning
confidence: 97%
“…For instance, Tiwari et al. (2022) reported that CHNPs– Lippia origanoides essential improved the acceptability, color, taste, and flavor of black cumin seeds after 18 months of storage. CHNPs with Pimpinella anisum essential oil improved rice seeds’ color, taste, and odor after 1 year of storage (Das, Singh, et al., 2021).…”
Section: Effects Of Chnps On Postharvest Productsmentioning
confidence: 99%
“…AFs contaminate different food commodities such as cereals, nuts and spices to damage human and animal health (Tiwari et al ., 2022; Vita et al ., 2022). AF (AFM1) has also been isolated from milk and milk products resulting from consuming contaminated animal feed (Assaf et al ., 2019; Guan et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%